Application of Crossword Learning Media to Increase Learning Interest of SMPN 1 Garut Students in IPS Subjects (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
Low interest in learning of students is a common problem in social studies learning. The lecture method that is still dominant is considered less relevant to the characteristics of Generation Alpha, who are more responsive to visual and interactive learning. This condition requires the presence of interesting learning media, one of which is crossword media. This study aims to measure the influence of crossword learning media on students' learning interests in social studies subjects. The method used is quantitative with a quasi-experimental design. The research sample was selected using purposive sampling techniques from class VIII of SMPN 1 Garut, namely classes VIII G and VIII H. The instruments used included interviews, pretests, posttests, learning interest questionnaires, observations, and reflections. Data were analyzed using validity, reliability, normality, homogeneity, the t-test, the Mann-Whitney test,the Pearson correlation test, and the simple linear regression test and supported by the SPSS version 27 device. The results of the study showed that crossword media can increase students' interest in learning by around 66.7%, especially in the aspects of active involvement and discipline. Although no significant correlation was found between posttest results and learning interest scores, changes in students' learning behavior were noticeable. This media is effective in encouraging interest in learning in affective and social contexts if supported by appropriate teaching strategies.